2019
DOI: 10.1007/s10668-019-00514-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived livelihood impacts and adaptation of vegetable farmers to climate variability and change in selected sites from Ghana, Uganda and Nigeria

Abstract: In the wake of deepened situations of changing climate, a clear understanding of the perceived impacts and adaptation of climate variability and change on livelihoods of vegetable farmers in Western and Eastern Africa, which is not readily available, is critical for sustainable vegetable production in Africa. Development planning for climate change vulnerability and adaptation assessment was utilised in the study. Using multi-stage sampling procedure, 193 vegetable farmers in selected sites prominent for veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
(25 reference statements)
4
15
0
Order By: Relevance
“…This result shows that farmers are well aware of climate change. This result is similar to Fadairo et al (2019), who also found that awareness of climate variability and change was high among vegetables farmers.…”
Section: Farmers' Perception Of Climate Changesupporting
confidence: 89%
See 2 more Smart Citations
“…This result shows that farmers are well aware of climate change. This result is similar to Fadairo et al (2019), who also found that awareness of climate variability and change was high among vegetables farmers.…”
Section: Farmers' Perception Of Climate Changesupporting
confidence: 89%
“…Indigenous vegetables farmers, therefore, adopt a number of adaptation strategies to mitigate the effect of climate change on their production activities. Although Fadairo et al (2019) examined the perceived likelihood impact and adaptation of vegetables farmers to climate change, their emphasis was not on indigenous vegetables which is the focus of this study. Their study advocated for locality-specific climate change adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top most priority given to prayer as a means of coping with conflict among the respondents is not uncommon in most West African countries where religion plays critical roles in daily survival of most households (Ogunlela and Mukhtar, 2009). This is also similar to the assertion of Egbe et al (2014) and Fadairo et al (2019) that prayer play important roles as a mechanism for coping with climate change among farmers in Nigeria. This finding shows farmers as desiring peace and not crisis.…”
Section: Perception Of Farmers Towards the State Enacted Anti-open Grsupporting
confidence: 86%
“…The relationship between climate change perception and livelihoods is both important and underresearched (Kolawole et al 2016;Fadairo, Williams, and Nalwanga 2019). Although less readily available in cross-sectional data sets than socioeconomic and demographic indicators such as age, wealth, and gender, data on livelihoods constitute a potentially powerful predictor of climate perception, framing climatic factors according to particular economic sensitivities.…”
Section: Climate Perception and Livelihoodsmentioning
confidence: 99%